2017
DOI: 10.1002/jssc.201601429
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-reinforced sol-gel based hollow fiber solid-phase microextraction for citalopram determination using response surface methodology

Abstract: The inclusion of a polyamidoamine dendrimer in a silica sol-gel yielded a solid nanosorbent that was used for the preconcentration, extraction, and determination of citalopram in hospital waste water, hemodialysis solution, and some drinking water. The method was developed by applying a novel nanosorbent for the solid-phase microextraction of citalopram, containing a silica sol-gel reinforced by polyamidoamine second-generation dendrimer, which was protected by a polypropylene hollow fiber. Plackett-Burman des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…However, it is complicated, labour‐intensive and time‐consuming to identify and isolate bioactive compounds from the numerous complex compounds in herb materials. To overcome these disadvantages, various techniques have been developed, including membrane separation , affinity selection ultrafiltration , and enzyme immobilization . For instance, Choi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is complicated, labour‐intensive and time‐consuming to identify and isolate bioactive compounds from the numerous complex compounds in herb materials. To overcome these disadvantages, various techniques have been developed, including membrane separation , affinity selection ultrafiltration , and enzyme immobilization . For instance, Choi et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is complicated, labour-intensive and time-consuming to identify and isolate bioactive compounds from the numerous complex compounds in herb materials. To overcome these disadvantages, various techniques have been developed, including membrane separation [14,15], affinity selection ultrafiltration [16], and enzyme immobilization [17]. For instance, Choi et al [18] successfully identified eupatilin from Artemisia argyi as a PPARα agonist inhibitor by using ultrafiltration, which has emerged in the recent decade as a new method to isolate bioactive compounds due to its simple operation and satisfactory high-throughput screening.…”
Section: Introductionmentioning
confidence: 99%
“…SPME, which involves the use of a thin polymer‐coated fiber for the extraction of analytes, has a wide variety of applications . SPME fibers have been prepared using various methods, that is, physical deposition , electrochemical deposition , and sol–gel techniques .…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of the sol–gel coating technique include ability to provide direct chemical bonding to the substrate, coatings with high porous structure, thermal, chemical, and solvent stability of the created sorbent coatings. These advantages of sol–gel coating techniques paved the way for its application in SPME popularly used in a variety of analytical fields including biomedical , environmental , food , etc. The introduction of sol–gel coatings in SPME by Malik et al.…”
Section: Introductionmentioning
confidence: 99%
“…stability of the created sorbent coatings. These advantages of sol-gel coating techniques paved the way for its application in SPME [5] popularly used in a variety of analytical fields including biomedical [6], environmental [7], food [8], etc. The introduction of sol-gel coatings in SPME by Malik et al [9] played a significant role in further expansion of the analytical scope of SPME and other microextraction techniques.…”
Section: Introductionmentioning
confidence: 99%